Peningkatan Pengetahuan dan Aktivitas Fisik Dalam Pengendalian Hipertensi di RT 09 Kelurahan Jembatan Kecil Kota Bengkulu - Bayu Anggi Pratama; Shelvia Purnama Pratiwi; Bambang S; Sucitra Fitri; Herwita Herwita; Asep Hadi Saputra; Pepi Guslenawati (Jurnal Pengabdian Mitra Persada, 2026)
Hypertension is a non-communicable disease that has become a public health problem due to its increasing prevalence and the risk of complications it causes. Low public awareness of early detection and the adoption of a healthy lifestyle are the main factors contributing to the difficulty of controlling hypertension at the community level. This community service activity aims to increase public knowledge and awareness of hypertension prevention and control through a promotive and preventive approach. The activity was carried out in RT 09, Jembatan Kecil Village, Singaran Pati District, Bengkulu City, using methods of early detection health checks, health education, and hypertension exercises. The target of the activity was adults and elderly people who had risk factors for hypertension. The results of the activity showed that of the 20 participants who underwent health checks, 10 were detected to have hypertension. Health education was able to increase the community's understanding of hypertension, risk factors, and the importance of regular blood pressure checks. The hypertension exercise was actively participated in by 33 participants and had a positive impact on the community's motivation to apply physical activity as non-pharmacological therapy. It can be concluded that this community service activity was effective in increasing community awareness, knowledge, and participation in hypertension control. Similar activities